Death Penalty Criticism and Its Relevance in Indonesia's Modern Criminal Justice System: A Normative Analysis of Law No. 1 of 2023 - Sona Asnawi; Agit Yogi Subandi; Mulyadi Mulyadi; Yandri Ahmad Rifandi; Nicodias Palasara (SEAN Institute, 2026)
Criminal law reform in Indonesia continuously seeks to balance retributive justice with the protection of human rights, particularly regarding the existence of the death penalty. This study aims to analyze the fundamental concept of capital punishment, examine scholarly criticisms of its implementation, and evaluate its relevance within the modern legal system. Employing a normative legal research method with a literature-based approach, this study analyzes primary and secondary legal materials related to policies governing the formulation and application of the death penalty. The findings reveal that the principal criticisms of capital punishment concern the lack of conclusive empirical evidence supporting its deterrent effect and the risk of irreversible judicial errors. From the perspective of modern law, a significant paradigm shift has occurred, whereby the death penalty is no longer positioned as a principal punishment but rather as a special and alternative sanction, as stipulated in Law Number 1 of 2023 concerning the Criminal Code. This transformation reflects an effort to reconcile criminal justice objectives with contemporary human rights standards. The study concludes that the death penalty remains relevant in the modern legal era only when applied as an ultimum remedium (last resort) for extraordinary crimes, accompanied by careful consideration of human rights principles, proportionality, and substantive justice.